Pengembangan Bahan Ajar Digital Menggunakan Heyzine Flipbook pada Topik Indonesiaku Kaya Hayatinya untuk Meningkatkan Hasil Belajar Peserta Didik - Mazaya Leila Nadhilah; Surti Kurniasih; Indri Yani (Mataram University, 2026)
The limited availability of interactive and technology-based teaching materials has become one of the factors contributing to low student engagement and suboptimal learning outcomes in elementary science and social science (IPAS) learning. Therefore, it is necessary to develop innovative digital teaching materials that are engaging, accessible, and aligned with students' learning needs. This study aimed to develop digital teaching materials using the Heyzine Flipbook on the topic of Indonesia's Rich Biodiversity and to determine their validity, practicality, and effectiveness in improving the learning outcomes of fifth-grade students at SDN Taman Pagelaran. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The trial subjects were 31 students from Class V-B. Data were collected through expert validation, pretest and posttest assessments, and questionnaires administered to both students and the teacher. The validation results indicated that the developed digital teaching materials were highly valid, with validation scores ranging from 98% to 100% from the subject matter experts, 91% from the language expert, and 95% from the media expert. The trial results demonstrated an improvement in students' learning outcomes, as indicated by an N-Gain score of 0.71, which falls into the high category. Furthermore, the students' responses reached 94%, while the teacher's response achieved 100%, resulting in an overall average of 97%, which is classified as excellent. Therefore, the digital teaching materials developed using the Heyzine Flipbook are considered valid, practical, and effective for use in fifth-grade elementary science and social science (IPAS) learning.